Zmiany w edukacji włączającej a sytuacja ucznia ze specjalnymi potrzebami edukacyjnymi = Changes in inclusive education and the situation of students with special educational needs - Skotnicka, Beata (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Inclusive education, even though present for many years in the educational space, is still a challenge for education policy. The purpose of the introduced changes is to best adapt the teaching process to the needs of all students. Designing and introducing changes is a long-term task, requiring the implementation of speci?c strategies and teaching solutions.
Keywords: edukacja włączająca; przestrzeń edukacyjna; czeń ze specjalnymi potrzebami edukacyjnymi; zmiana; inclusive education; educational space; students with special educational needs; change